Assessment of the morphological composition of secondary construction waste from destruction - Shvydkyi, Dmytro; Shvets, Vitaliy; Sokolenko, Kostiantyn; Sokolenko, Valeriy (Academic journal Industrial Machine Building Civil Engineering, 2025)
The issues of post-war reconstruction of territories and settlements that suffered extensive damage as a result of hostilities are considered. Rational design and construction solutions are proposed that allow maximum use of the foundations of destroyed buildings for further reconstruction. It is determined that the planning solutions for the quarter development of industrial cities are imperfect and require updating in accordance with modern principles. A solution that significantly reduces the amount of work involved in dismantling the underground structures of buildings is to use them for the construction of new reconstruction objects. A combined solution is proposed for the joint use of the foundation array of a destroyed building and a monolithic grillage on bored piles. The use of diamond drilling technologies allows for the effective installation of piles in complex, swampy areas. It is proposed to construct the structure in the form of a system of soil foundation, artificial foundation, connected by a system of piles and foundation frames.
Keywords: region; secondary construction waste; destruction; morphological composition; recycling; utilization; processing; waste management